2014
DOI: 10.1097/ncc.0b013e3182888b14
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Diabetes Self-Management in Older Adults Receiving Chemotherapy

Abstract: Oncology nurses need to be aware of the impact cancer treatment can have on the performance of diabetes self-management activities in adults. Future research needs to test interventions that may assist patients with diabetes and cancer in managing both diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 50 publications
1
27
0
1
Order By: Relevance
“…For patients with comorbid cancer and diabetes, the adverse outcomes highlighted in this review include higher mortality rates [36], consistent with findings in several studies [7,8,11,16] and poor adherence to DM medications [31,34,35] as reported by Hershey and colleagues [11]. …”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…For patients with comorbid cancer and diabetes, the adverse outcomes highlighted in this review include higher mortality rates [36], consistent with findings in several studies [7,8,11,16] and poor adherence to DM medications [31,34,35] as reported by Hershey and colleagues [11]. …”
Section: Discussionsupporting
confidence: 84%
“…Consequences include: increased mortality [7,8], higher infection rates [9,10], higher hospitalisation rates [10], worse physical function [11] and poorer prognosis [12,9]. Potential reasons for these poorer outcomes include: prioritising cancer treatments over DM self-management activities [11,13]; increased prevalence of and/or under recognition of hyperglycaemia [14]; and clinicians lacking skills in managing both these complex conditions [14,15]. Sub-optimal DM management during cancer care can result in worsened glycaemic control [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the importance of comorbidities has not been well established in older patients with AML. However, it has been shown that AML cancer survivors who have comorbid disease(s) experience lower levels of QOL, (45) have poorer physical function, and less able to self-manage their disease (46). The assessment of comorbidities prior to treatment is critically important to better facilitate choice of treatment options.…”
Section: Comorbidity Measures In Amlmentioning
confidence: 99%